Análise de Distorção Harmônica em Usina Fotovoltaica Conectada à Rede: Estudo de Caso da USF do Câmpus de Palmas da Universidade Federal Do Tocantins – UFT - Silva, Izabela Gonzaga da (Universidade Federal do Tocantins, 2022)
This paper has the purpose of analyzing the quality of photovoltaic solar energy, located on the university campus of Palmas-TO, Federal University Tocantins through harmonic distortion analysis. For this, a theoretical foundation is presented about distributed generation, energy quality, photovoltaic solar energy systems, energy and harmonic inverters, and the current national and international norms and regulations on the subject, being also carried out a case study related to harmonic distortion in the university's photovoltaic solar plant, that is, the motor of a transformation of the plant, located in Block J, was carried out through the Fluke 1738 power quality study, which wants to obtain the indicators of distortion of the photovoltaic generator so that later the data could be performed in order to observe the values of agreement of the data obtained with the references presented in the norms, regulations and standards in force. From this analysis concluded, the equipment is within the expected standards